Суверенные Права Экваториальной Страны На Геостационарную Орбиту (ГСО), Поскольку Природные Ресурсы Ограничены (Sovereign Rights of an Equatorial Country to the Geostationary Orbit (GEO) Due to Limited Natural Resources) - Farhani, Athari; Azizah, Faiqah Nur (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This study discusses the injustice experienced by equatorial countries, especially Indonesia, in utilising geostationary orbit (GEO), which is geographically located above the equator. GEO is a limited and strategic natural resource, but is currently dominated by developed countries through the first-come, first-served principle, which is considered unfair and widens the global gap between developing and developed countries. This study aims to examine the sovereign rights of equatorial countries to GEO and to encourage recognition of these rights within the framework of international space law. This study uses a qualitative method with a literature approach and international legislation studies, specifically examining the provisions of the 1967 Outer Space Treaty and the 1976 Bogota Declaration. The study results indicate that although the Bogota Declaration is considered to conflict with Article 2 of the Outer Space Treaty, it is urgent to revise or adjust the international agreement to make it fairer for equatorial countries. In conclusion, as an equatorial country, Indonesia has a moral and geographical basis to demand recognition of sovereign rights over GEO as a limited resource within its territorial boundaries.Keywords: Geostationary Orbit; Equatorial Country; Sovereign Rights